Investigation of Noise Effects for Different Quantum Computing Architectures in IBM-Q at NISQ Level - Yetis, Hasan; Karakoes, Mehmet (Institute of Electrical and Electronics Engineers Inc., 2021)
Today, all the implemented quantum computers are in Noisy Intermediate-Scale Quantum (NISQ) level. In such quantum computers, when circuit length and size increase, the results become less reliable because of the increasing effect of noise. The noise is an important factor that should be handled in NISQ level quantum computers. In this study, we investigate the noise factor on 5 qubit IBM-Q computers for basic circuits. For this purpose, existing 5 qubit IBM-Q computers with different architectures are examined. Then quantum circuit equivalents corresponding to basic logic gates such as XOR, AND, and OR are presented. Quantum circuits created for XOR, AND, and OR are run 10 times on different quantum computers of 5 qubits named Santiago, Athens, Valencia, Vigo, Ourance, and IBMQX2. Statistical information such as std., mean is obtained from the results. The consistency of the results obtained and their difference from the optimum result are discussed. As a result of the study, there is no contradiction in the results obtained with quantum volume. Studies show that even small growths in XOR, AND, and OR circuits can lead to a big deflection in results. © 2021 IEEE.
25th International Conference on Information Technology, IT 2021 -- 16 February 2021 through 20 February 2021 -- Zabljak -- 168281
Keywords: Computation theory; Computer architecture; Qubits; Basic circuits; Basic logic gates; Increasing effect; Noise effects; Noise factor; Quantum circuit; Quantum computing architectures; Statistical information; Computer circuits